Feeling of self-worth in healthy premenopausal women—relationships with menstrual cycles and ovulation over 1-year in the prospective ovulation cohort - Nahid Shirazian; Sonia Shirin; Dharani Kalidasan; Jerilynn C. Prior (PLoS ONE, 2025)
Self-Worth is an over-arching evaluation of a person’s sense of individual value. Self-worth, however, is an underappreciated concept. It has rarely been reported related to physiological data; we found no studies related to the menstrual cycle or ovulation. It is also unclear if Self-Worth is a stable trait or a variable state. We sought to discover if “Feeling of Self-Worth” (as recorded daily) was related to cycle phases and ovulation of spontaneous menstrual cycles (without hormonal contraception) in healthy premenopausal women over one-year in data from the Prospective Ovulation Cohort. Participating women were invited to complete the Menstrual Cycle Diary© (Diary©) daily; it describes cycle-related and other comprehensive everyday life experiences including negative moods as well as changes from each person’s usual Feelings of Self-Worth. Women recorded their Feeling of Self-Worth on a 5-level ordinal scale as a letter translated to a number originally centered on their usual feeling (U = 3) with two higher and two lower (letters) levels. The validated Quantitative Basal Temperature© (QBT©) method was used to assess ovulation and luteal lengths. Fifty-three healthy, community dwelling, normal-weight, non-smoking premenopausal women mean age 33.9 (95% CI 32.4, 35.5) years old were studied. All participants were first required to document two consecutive normal-length (21–36 days) and normally ovulatory (luteal length ≥10 days) cycles before enrolment. Each participant completed the Diary© and QBT© records daily over a mean of 13 cycles (minimum = 8). During the study, cycle lengths were mean 28.04 (95% CI 27.80, 28.28) days with 71% of all cycles being normally ovulatory, 26% having short luteal phases (SLP, LL < 10 days) and 2.6% being anovulatory. Results in all women and all cycles showed that the mean annual Feeling of Self-Worth was 3.01 (95% CI 2.94, 3.09), thus very tightly related to their usual Feeling of Self-Worth. There were only small, inconsistent differences between Feeling of Self-Worth in the follicular versus luteal phases comparing normally ovulatory versus all ovulatory cycles (including those with short luteal phases). Analysis of Self-Worth within the 46 women having both normally ovulatory and ovulatory disturbed cycles (short luteal and anovulatory) showed that it was slightly lower in these women’s normally ovulatory cycles (P = .03). Principal Components Analysis of all Diary© data showed that Feeling of Self-Worth was positively related to Interest in Sex and Feeling of Energy (together explaining 9% of all variance). In addition, Feeling of Self-Worth had a significant, negative loading on the Negative Mood Factor (that explained 14.2% of total variance). These data suggest that Feelings of Self-Worth in this comprehensive menstrual cycle and ovulation dataset in healthy women were not related menstrual phases and ovarian hormone levels.